An assessment of a network approach in a project- based organization – a case study of a global engineering service provide - Nowakowska-Cicio, Małgorzata (Ocena sieciowości organizacji o strukturze kontraktowej – studium przypadku globalnego dostawcy usług inżynieryjnych, 2020)
This paper deals with the phenomenon of networks in operations research using the example of a selected organization. The main research objective is to analyse and evaluate the network implications in the sector of global design and engineering service providers. In the course of the research, one representative organization in the sector was subjected to research in accordance with the adopted methodology using structured questionnaires. After a literature review, a model of strategic analysis in a network approach was chosen as a starting point for preparing the methodology. The case study clearly showed that the company cannot be classified as a network organization according to the adopted methodology despite the noted network qualities. Therefore, it is legitimate to indicate severe contradictions in the three areas examined: environment, strategy and organization. Future research could be twofold: related to organizational structures and strategies evolution as well as the incubation of more accurate research methods
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 10, s. 79-87